SLM equipment is melted to dedicated selectivity of dentistry - TANG BAO; PANG ENLIN; SUN FEN; ZENG GANG; KONG LONGHUI (2016)
The utility model provides a SLM equipment is melted to dedicated selectivity of dentistry, including molding system, optical system, material transition bin and powder recovery system, optical system, material transition bin and powder recovery system all connect on molding system, molding system is used for printing the metal tooth, optical system provides laser to molding system, is processed into the metal tooth with the metal powder, material transition bin is used for providing the metal powder to molding system, powder recovery system is used for retrieving molding system's surplus metal powder. 本实用新型提供了种牙科专用的选择性融化SLM设备，包括成型系统、光学系统、物料过渡仓和粉末回收系统，光学系统、物料过渡仓和粉末回收系统均连接在成型系统上；成型系统用于打印金属牙；光学系统对成型系统提供激光，将金属粉加工成金属牙；物料过渡仓用于向成型系统提供金属粉；粉末回收系统用于回收成型系统的剩余金属粉。